STRATEGIC FINANCIAL MANAGEMENT IN THE FACE OF BOYCOTTS: UNDERSTANDING THE IMPLICATIONS ON FINANCIAL ACCOUNTING PRACTICESFOR COMPANIES DEALING WITH ISRAELI GOODS - Nurdin I. Muhammad; Hajar Mukaromah; A Fadel Muhammad; Loso Judijanto; Bahrun Thalib (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study, conducted in the past tense, delved into the complexities of Strategic Financial Management amid product boycotts, with a specific focus on the implications for financial accounting practices in companies involved in the trade of Israeli goods. Examining historical perspectives on boycotts, the research elucidated the dynamic role of financial accounting in international trade, defining and contextualizing Strategic Financial Management as a vital alignment between financial strategies and geopolitical factors. Employing a case study approach and qualitative analysis methods, the study explored the multifaceted impact of boycotts on financial accounting practices, uncovering actionable strategies such as risk mitigation through diversification and contingency planning, adaptive financial reporting practices, and stakeholder engagement.